JARINGAN SOSIAL PENAMPUNG BARANG BEKAS di Nagari Padang Gelugur Kecamatan Panti Kabupaten Pasaman - -, Desrita - (Pendidikan Sosiologi, 2014)
This research baceground is much people in padang gelugur village that involved or receiver network of second thand goods compare than other village. Person that involved on this receive network is 1 person as receiver of secondhand goods, 6 person as anak galeh who receiver of secondhand goods, 2 person as porter in received. This researt the purpose to describe deceiver network of secordhand goods in Padang Gelugur Subdistrict Panti, Regency Pasaman. The theory used is Sosial network Theory. J.A Barnes. This research uses a qualitative approach with descriptive type. The sampling technique used snowball sampling. Types of primary and secondary data. The collection of data through observation, interviews, and documentation. While the data analysis is data reduction, data presentation, and verification (conclusion). Based on result of research, can be concluded (1) view from receiver network of secondhand goods in padang gelugur village, such as (a) (anak galeh) (b) receiver of secondhand goods (2) basic form of network such as (a) sociable (b) believable (c) expectation (d) interest